Curse of the demon - James, M. R. 1862-1936; Parker, Clifton 1905-1989 (Columbia Tristar Home Entertainment, 2002)
When a psychologist's colleague is murdered, he denies that it is the work of the devil, until he himself becomes the next target.
Orig.: UK 1957. - Sprache: Engl. - Untertit.: Engl., Franz., Japan. - Enth. Special features
Keywords: Demonology -- Drama; Psychologists -- England -- Drama; Feature films; Horror films; Video recordings for the hearing impaired